Dimerization of Acetic Acid in the Gas Phase-NMR Experiments and Quantum-Chemical Calculations - Socha, Ondřej; Dračínský, Martin (Molecules (Basel, Switzerland), 2020)
Due to the nature of the carboxylic group, acetic acid can serve as both a donor and acceptor of a hydrogen bond. Gaseous acetic acid is known to form cyclic dimers with two strong hydrogen bonds. However, trimeric and various oligomeric structures have also been hypothesized to exist in both the gas and liquid phases of acetic acid. In this work, a combination of gas-phase NMR experiments and advanced computational approaches were employed in order to validate the basic dimerization model of gaseous acetic acid. The gas-phase experiments performed in a glass tube revealed interactions of acetic acid with the glass surface. On the other hand, variable-temperature and variable-pressure NMR parameters obtained for acetic acid in a polymer insert provided thermodynamic parameters that were in excellent agreement with the MP2 (the second order Møller-Plesset perturbation theory) and CCSD(T) (coupled cluster with single, double and perturbative triple excitation) calculations based on the basic dimerization model. A slight disparity between the theoretical dimerization model and the experimental data was revealed only at low temperatures. This observation might indicate the presence of other, entropically disfavored, supramolecular structures at low temperatures.
Keywords: vodíková vazba; Gases; Algorithms; chemické modely; Pressure; tlak; magnetická rezonanční spektroskopie; plyny; Quantum Theory; NMR spectroscopy; Models, Chemical; quantum-chemical calculations; hydrogen bonding; kyselina octová; kvantová teorie; Acetic Acid; algoritmy; Hydrogen Bonding; Magnetic Resonance Spectroscopy; phase transitions; carboxylic acids